Goalie and scoring analysis : MOL, Mestis and Liiga - Kontsas, J.; Lehtola, J. (2014)
The purpose of this thesis is to determine whether the repetition of different scoring situations and goaltenders actions differ between different levels of men`s ice hockey. Furthermore the purpose is to find the skills and knowledge that are needed to succeed in high level. When starting the research, two questions were made: 1. Does lower skill level of an ice hockey goaltender affect his actions in different scoring situations? 2. Does higher level of hockey affect on what type of scoring situations occur in a game? First part of the research, done in 2010, we marked down all shots from 30 ice hockey games. Ten games from each of these leagues or tournaments: SM-Liiga (Finland 1st) season 2009-2010, Men´s Ice Hockey World Championships 2009, and NHL (National Hockey League) season 2009-2010. All the subjects were males aged 17-35 years. Every game we marked had numerous skaters, and two goalies. All the marked games were selected randomly. Second part and the core of this research, done in 2013-2014, consisted same type of research that was done in 2010. Shots and goaltender actions from ten games were marked and analyzed from Hungarian 1st league MOL, season 2013-2014, and from Finnish 2nd league Mestis, season 2013-2014. All of the collected data was analyzed and then compared in order to find answers, if there were differences between different levels of ice hockey leagues, as stated in study questions.